(untitled) (Current Horticulture, 2024)
The experiment was conducted to assess cowpea [Vigna unguiculata (L.) Walp] varieties at five farmers’ fields of the Panchmahal district in Gujarat during 2014-15 and 2016-17. The five varieties were taken to see their performance. There was a significant difference among varieties in growth, flowering, fruiting, yield and economics. There was the maximum germination (85.44%), number of leaves at first harvesting (36.24), root length (24.88 cm), root weight 60 days after sowing (26.73g), pod weight (9.23g), pod length (31.56) and pod diameter (2.56 cm) after 60 days of sowing in Kashi Kanchan, whereasminimum days of flowering (41.44 days) and fruit harvesting (51.78 days) were recorded in Kashi Unnati. The maximum number of cluster/plant (9.97), number of pods/plant (30.61), gross return (?1,28,856), net return (?94,781), and cost benefit : ratio (3.78) were also recorded in Kashi Unnati.